Efektivitas Hukum Pelestarian Bangunan Dan Lingkungan Cagar Budaya Di Kota Denpasar - I Putu Sastra Wibawa; Mahrus Ali (Jurnal Hukum IUS QUIA IUSTUM, 2020)
The Regional Regulation on Cultural Heritage of Denpasar City has been in effect for 5 years, it is very important to assess its effectiveness. There are two problems raised in this study. First, how effective is the Denpasar City Cultural Heritage Regional Regulation? Second, what is the strategy to achieve the effectiveness of the Denpasar City Cultural Heritage Regional Regulation? Data analysis was carried out both from primary data from the results of interview data, and analysis of secondary data in the form of primary and secondary legal materials. Therefore, this research can be called a research that uses mixed methods or is categorized as a socio-legal research. The results of the study conclude, firstly, regarding the effectiveness of the Regional Regulation on Cultural Heritage of Denpasar City, it can be reviewed from three sides, namely the role of regional officials, the rule of law, and legal awareness of the community. Second, the Regional Regulation on Cultural Heritage of Denpasar City is still not effective in regulating and implementing it in supporting the preservation and management of cultural heritage in Denpasar City. To achieve the legal effectiveness of the Denpasar City Cultural Heritage Regional Regulation, several strategies can be pursued, among others, the legal aspect strategy, the institutional aspect strategy, the physical aspect strategy and the financial aspect strategy.